2007
DOI: 10.1562/0031-8655(2001)0740424mopaio2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Offers Protection Against Induction of Cyclobutane Pyrimidine Dimers and 6-4 Photoproducts by UVB in Cultured Human Melanocytes¶

Abstract: The goal of this investigation was to correlate the melanin content in human pigmentary cells with the generation of UVB‐induced photoproducts and to examine the relationship between the melanin content and the removal of the photoproducts. Cultured melanocytes from light‐skinned individuals synthesized less melanin and produced more cyclobutane pyrimidine dimers and 6–4 photoproducts upon UVB exposure than did melanocytes from black skin. Tyrosine‐stimulated melanogenesis provided protection against DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…then thymine dimers were detected in 100 ng of DNA by immunoslot blots using the aforementioned antibody, as described by Smit et al 6 The quantitation of immunoslot blots was performed with a densitometer and the software ImageQuant from Molecular Dynamics (Redwood City, Calif).…”
Section: Pyrimidine Dimers and Lipid Peroxidationmentioning
confidence: 99%
“…then thymine dimers were detected in 100 ng of DNA by immunoslot blots using the aforementioned antibody, as described by Smit et al 6 The quantitation of immunoslot blots was performed with a densitometer and the software ImageQuant from Molecular Dynamics (Redwood City, Calif).…”
Section: Pyrimidine Dimers and Lipid Peroxidationmentioning
confidence: 99%
“…Most melanins appear to be mixed polymers based on indoles but contain variable amounts of other preindole products of the synthetic pathway 14 . Many studies have demonstrated that melanin plays a role as a photoprotector against radiation in organisms and cells, especially in the UV region of the spectrum 15,16 . Melanin is thought to filter out UV radiation and scavenge reactive oxygen species (ROS), thereby reducing UV damage in vivo 17 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The major role of cutaneous melanin is protection against the harmful actions of solar radiation, by acting as a filter against ultraviolet radiation (UVR), preventing its penetration and genotoxicity (formation of UV-induced DNA dimmers). [11][12][13][14][15][16] Melanin also neutralizes reactive oxygen species (ROS) generated mostly by UVA, through its antioxidative and free-radical scavenging actions. 13,16,17 Overall, melanin protects against epidermal carcinogenesis or melanomagenesis.…”
mentioning
confidence: 99%